P147 Adding a Domestic Abuse Routine Prompt to the GUM Proforma: But Are we Asking the Question?. (30th June 2016) - Sacks, Rachel; Lavida, Anthi; Mears, Alison
Abstract : Background/introduction: In July 2015, a routine domestic abuse (DA) prompt was introduced in a busy, walk-in, inner-London, genitourinary medicine (GUM) clinic. DA guidelines, proforma and management flowchart were devised. Tiered training was/is provided at a basic level for all staff and in-depth for Sexual Health Information Protection team (SHIP) and DA champions.Auditable outcomes: DA question asked where safe (Target 100%), (SAFE: quiet/confidential space, seen alone, no child > 18 months present, professional interpreter if necessary), Complete DA proforma if DA disclosed (100%), Patient information leaflet (PIL) given if DA > 3/12 ago/no on-going risk (100%), Offered SHIP referral for risk assessment if DA < 3/12 or on-going risk (100%), DA disclosures correctly coded (100%). Aim(s)/objectives: Audit whether DA routine prompt asked, proforma completed, initial management pathway followed and disclosures coded. Methods: Data collected (notes review) on 100 consecutive, new, walk-in, GUM patients > 18 years-old, from 1 st October 2015. Results: 59 female, 41 male. 91% patients asked about DA. 9 not asked: 5/41 (12.1%) male, 4/59 (6.8%) female. 9/9: no reason documented explaining omission. 5/91 (5%) disclosed DA (all female). DA proforma completed in 3/5 (60%) (1 patient declined further discussion). 1/4 (25%) had current/on-going risk and referred to SHIP. 3/4 DA occurred > 3/12 ago/no on-going risk: 1 accepted, 1 declined, 1 not offered PIL. 2/5 (40%) DA disclosures coded correctly (using in-house code). Discussion/conclusion: High enquiry rate (male patients less likely to be asked). DA protocol/flow chart followed in the majority of cases (proforma completion and referral to SHIP). There were low levels of accurate coding.